MODEL KONSEPTUAL INTEGRASI AKUNTANSI LINGKUNGAN KE DALAM PELAPORAN KEUANGAN: IMPLIKASI BAGI AKUNTABILITAS DAN PRAKTIK AKUNTANSI MODERN - Astuti, Novising Dewi; Malau, Eve Ida; Bahantwelu, Maria Immaculata (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This research aims to develop a conceptual model for integrating environmental accounting into financial reporting as an effort to strengthen accountability and promote sustainable accounting practices. Environmental accounting is seen as a strategic instrument capable of connecting the economic and ecological dimensions within the context of modern organisational reporting. Through a qualitative approach based on theoretical review and analysis of current literature, this research examines the development of environmental accounting thought and implementation across various sectors, and identifies the remaining obstacles in its integration process. The study results indicate that the implementation of environmental accounting in financial reporting is not yet optimal due to limitations in reporting standards, low understanding of sustainability issues among accounting practitioners, and the absence of binding regulations. Nevertheless, integrating environmental information into financial reporting has proven to enhance transparency, strengthen public accountability, and broaden companies' social legitimacy. The proposed conceptual model positions accountants as agents of change who play an active role in connecting the economic, social, and environmental dimensions through an integrated reporting system. Theoretically, this research enriches the traditional financial reporting paradigm towards sustainability reporting, while practically providing direction for the development of policies and the competence of the accounting profession in supporting more environmentally responsible governance.